DTC-ANN-2-level hybrid by neuronal hysteresis with mechanical sensorless induction motor drive using KUBOTA observer - Dris Ahmed; Bendjebbar Mokhtar; Belaidi Aek (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this paper, DTC is applied for two-level inverter fed IM drives based on neuronal hysteresis comparators and The Direct Torque Control (DTC) is known to produce quick and robust response in AC drive system. However, during steady state, torque, flux and current ripple. An improvement of electric drive system can be obtained using a DTC method based on ANNs which reduces the torque and flux ripples, the estimated the rotor speed using the KUBOTA observer method based on measurements of electrical quantities of the motor. The validity of the proposed methods is confirmed by the simulation results.The THD (Total Harmonic Distortion) of stator current, torque ripple and stator flux ripple are determined and compared with conventional DTC control scheme using Matlab/Simulink environment.